PENERAPAN ACCRUAL ACCOUNTING DALAM SEKTOR PUBLIK - Frisky Jeremy Kasingku (UNKLAB Business School, 2022)
The purpose of this article is to elaborate the implementation of the accrual accounting system with rises concept of New Public Management (NPM). Cash-based accounting systems have been used by the public sector, but with the existence of NPM, some countries have begun to implement accrual accounting. For this reason, this article discusses the process of implementing an accrual accounting system in several countries along with the challenges and approaches used for the accrual accounting implementation process. A literature review is carried out to discuss the topic in accordance with the purpose of this article. As a result, the process of implementing accrual accounting in several countries requires good analysis, prudence in implementation, along with an internalization process. To be able to implement an accrual accounting system, public sector readiness is needed. Keywords: Accrual Accounting, New Public Management, Public Sector Tujuan dari artikel ini adalah untuk mengelaborasi penerapan sistem akuntansi akrual dengan adanya New Public Management (NPM). Sistem akuntansi berbasis kas telah digunakan oleh sektor publik, tapi dengan adanya NPM, beberapa negara mulai menerapkan akuntansi akrual. Untuk itu, artikel ini membahas proses penerapan sistem akuntansi akrual dibeberapa negara beserta tantangan dan pendekatan yang digunakan untuk proses implementasi akuntansi akrual tersebut. Tinjauan literatur dilakukan untuk membahas topik sesuai dengan tujuan dari artikel ini. Hasilnya, proses penerapan akuntansi akrual di beberapa negara membutuhkan analisa yang baik, kehati-hatian dalam implementasi, beserta proses internalisasi. Untuk dapat menerapkan sistem akuntansi akrual, kesiapan sektor publik dibutuhkan. Kata kunci: Akuntansi Akrual, New Public Management, Public Sector